Weaving Wayang Klithik into Gotanjung Village’s Sedekah Bumi through The Sacred Thread - Selviawati, Evi; Syahrial, Syahrial (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Wayang klithik, a two-dimensional wooden puppetry tradition, is found in several regions in Central and East Java. In Gotanjung Village, Pati Regency, Central Java, wayang klithik is performed during sedekah bumi, a traditional ceremony that is commonly held by Javanese communities. Grounded in Lord’s (1960) theory on the origin of oral tradition, this research investigates the roots and mechanisms behind the sacrality of wayang klithik in the context of Gotanjung Village. In addition, the analysis adopts Vansina’s (1985) theoretical approach to oral tradition to explore more deeply why wayang klithik in Gotanjung Village has become an inseparable element of sedekah bumi, and how its ritual significance is manifested within the framework of community beliefs and cultural values. Using an ethnographic approach, data were collected through field observations, interviews with key informants, and focus group discussions. The data were analyzed through narrative and conversational analysis to ensure alignment with the community’s perspective. The findings indicate that the history of wayang klithik puppet-making in Gotanjung strongly influenced its sacredness. In terms of ritual significance, wayang klithik serves as an offering to honor the village's founding ancestors and reinforces the core values embedded within the series of rituals in the sedekah bumi.